Interfacial-layer-free growth of yttrium oxide on germanium by understanding initial surface reactions - Liu, Z. Q. (2013)
In this study, we investigate the surface and interfacial reactions involved in the growth of yttrium oxide through the oxidation of yttrium metal on germanium. Our combined understanding of the oxidation and interfacial reactions allows us to introduce a layer-by-layer method to grow an interfacial-layer-free yttrium oxide on germanium at room temperature, which has previously proven to be difficult. During initial growth, we show evidence that yttrium germanide provides the lowest kinetic pathway in the formation of the yttrium germanate interfacial layer and explain how this pathway can be avoided using our layer-by-layer method. This method can possibly be used to achieve interfacial-layer-free growth for other metal oxides on semiconductors.